The ability to automate the processing of digital portraits - Чеботарева, Ирина Борисовна; Захарченко, Вероника Владимировна (Technology audit and production reserves, 2013)
Nowadays, it is difficult to imagine a book, a magazine, an advertisement or a product cover without an illustration. Very often it is a photo, namely, a portrait. In order to reduce the processing time of such photos, this article defines the main defects, such as: - color defects; - lack of sharpness, blurred motion; - lack of contrast; - lack of brightness. Thereafter, the sequences of action were developed for each defect, i.e. the algorithms which eliminate these disadvantages the most accurately. In conclusion, we put forward a method for automating each algorithm in order to accelerate retouching and selection of photographs. The researches have shown that the automated portrait processing, in comparison with the manual one, requires 15 times less time consumption